Income distribution and macroeconomics - Oded Galor; Joseph Zeira (Brown University, Department of Economics, 2013)
This paper analyzes the role of income distribution in macroeonomic analysis. The study demonstrates that the long-run equilibrium depends on the initial distribution of income. In accordance with empirical evidence concerning the correlation between income distribution and output, an economy that is characterized by a relatively equal distribution of wealth is likely to be wealthier in the long run. The study may, therefore, provide an additional explanation for the persistent differences in per-capita output across countries. Furthermore, the paper may shed light on cross-countries differences in macroeconomic adjustment to aggregate shocks.
Keywords: O33; I10; 330; Wealth distribution; income distribution; growth; capital market; imperfections